Improving yield and profit in smallholder oil palm fields through better agronomy - Hendra Sugianto; Christopher R. Donough; Juan P. Monzon; Sunawan; Iput Pradiko; Ya Li Lim; Fatima A. Tenorio; Gonzalo Rizzo; Suroso Rahutomo; Fahmuddin Agus; Setiari Marwanto; Maja Slingerland; et al. (Agricultural Systems, 2025)

The interactive antimicrobial activities of selected South African Terminalia spp. extracts in combination with conventional antibiotics against methicillin and β-lactam resistant pathogens - Muhammad Jawad Yousaf Zai; Matthew James Cheesman; Ian Edwin Cock (South African Journal of Botany, 2024)

Guiding oil palm intensification through a spatial extrapolation domain framework - Fahmuddin Agus; Fatima A. Tenorio; Shofia Saleh; Dwi Kuntjoro G. Purwantomo; Rahmah D. Yustika; Setiari Marwanto; Suratman; Manjit Singh Sidhu; James Cock; Suan Pheng Kam; Thomas Fairhurst; Juan I. Rattalino Edreira; et al. (Agricultural Systems, 2024)

A scheme for distribution of genetically improved oil palm plants well suited to local conditions - James H. Cock; Iván M. Ayala-Diaz; Hernán M. Romero (Agricultural Systems, 2023)

First things first: Widespread nutrient deficiencies limit yields in smallholder oil palm fields - Hendra Sugianto; Juan P. Monzon; Iput Pradiko; Fatima A. Tenorio; Ya Li Lim; Christopher R. Donough; Sunawan; Suroso Rahutomo; Fahmuddin Agus; James Cock; Joni Amsar; Rana Farrasati; et al. (Agricultural Systems, 2023)

Operations research and machine learning to manage risk and optimize production practices in agriculture: good and bad experience - James Cock; Daniel Jiménez; Hugo Dorado; Thomas Oberthür (Current Opinion in Environmental Sustainability, 2023)

Strategies for managing diseases in non‐native shrimp populations - James Cock; Marcela Salazar; Morten Rye (Reviews in Aquaculture, 2017)
The shrimp industry is now largely based on Litopenaeus vannamei . Current strategies for disease management in Asia emphasizing exclusion and eradication with strict quarantine and importation protocols have not been effective in controlling disease epidemics. New diseases have been introduced on illegal importations; commercial shrimp populations are derived from imported SPF stocks susceptible to endemic diseases; and local breeding programmes are based on populations not resistant to a range of diseases. Broodstock are largely poorly adapted to local conditions and repeated disease epidemics occur. Strategies for disease management should concentrate on: (i) minimizing the risk of introducing new diseases to the region; (ii) development of populations more resistant to endemic diseases; and (iii) better management practices that minimize the likelihood of serious epidemics and delay infection, but do not depend on attempts to eradicate diseases already present. This can be implemented by building on the better management practices already established in the region and in addition: (i) applying strict quarantine procedures for diseases not reported in the region whilst making the processes sufficiently agile to reduce illegal introductions; (ii) eliminating standard rigid importation protocols and tailoring protocols in accordance with the disease situation of both the country of origin and destination; (iii) increasing genetic variation available within Asia by public sector support for programmes to enlarge the pool of genetic variation and encouraging collaboration with breeding programmes that encompass a broad genetic base; (iv) establishing selection programmes that permit reincorporation of animals exposed to disease into the breeding nucleus; and (v) establishing propagation systems that provide growers with high health status stocks without requiring overly strict SPF certification of facilities.

Getting into hot water: sick guppies frequent warmer thermal conditions - Ryan S. Mohammed; Michael Reynolds; Joanna James; Chris Williams; Azad Mohammed; Adesh Ramsubhag; Cock van Oosterhout; Jo Cable (Oecologia, 2016)